A New Legal Concept for Understanding the Essence of Production and Consumption Waste: A View from Russia - Aleksey Anisimov; Dmitriy Motorin (Revista Direito GV)
Abstract Recently, production and consumption waste has been recognized as a distinct legal category in the environmental law of the Russian Federation. This regulatory category has been changed several times within a short period. The study evidences that these changes were ontological, resulting from a change in approach to the distinction of waste from other results of economic activity. In practice, these changes introduced new characteristics into the concept of waste, each of which is related to one of the approaches to understanding the essence of waste identified by the authors of the article. The article reveals handicaps of earlier and contemporary approaches to understanding the legal essence of waste in Russia. Based on the results of the study, a new subjective approach is proposed. This approach can serve as a starting point for shaping a new conceptual understanding of waste able to improve environmental law and promote quality enforcement.